Twitter, Team GB and the Australian Olympic Team: representations of gender in social media spaces - Litchfield, C.; Kavanagh, E. (Sport in Society: Cultures, Commerce, Media, Politics, 2019)
Twitter is used by athletes, sporting teams and sports media to provide updates on the results of sporting events as they happen. Unlike traditional forms of sports media, online sports media offers the potential for diverse representations of athletes. The current study examined gender in social media coverage of the 2016 Olympic Games using a third wave feminist lens. The analysis focused on the Twitter pages of `Team GB` and the `Australian Olympic team` and the sports stories and images posted during the Rio Olympic Games. Despite a number of traditional differences in the ways that male and females were represented being present, such as the presence of `active` images of male athletes accompanying sports stories and the presence of infantalization in the language used to represent female performers, this analysis demonstrated significant strides forward in terms of the quantity of coverage received by women in online spaces. It further highlights virtual platforms as dynamic spaces for the representation of women athletes.